Phosphatidic acid metabolism in rat liver cell nuclei. Issue 7 (21st February 2013) - Gaveglio, Virginia L.; Pasquaré, Susana J.; Giusto, Norma M.
Abstract : The aim of the present research was to analyze the pathways for phosphatidic acid metabolism in purified nuclei from liver. Lipid phosphate phosphatase, diacylglycerol lipase, monoacylglycerol lipase and PA‐phospholipase type A activities were detected. The presence of lysophosphatidic acid significantly reduced DAG production while sphingosine 1‐phoshate and ceramide 1‐phosphate reduced MAG formation from PA. Using different enzymatic modulators (detergents and ions) an increase in the PA metabolism by phospholipase type A was observed. Our findings evidence an active PA metabolism in purified liver nuclei which generates important lipid second messengers, and which could thus be involved in nuclear processes such as gene transcription. Abstract : ► DAG, MAG, LPA and WSP are produced from PA in liver nuclei. ► LPPs, DAGL, MAGL and PA‐phospholipase type A activities are demonstrated. ► LPA competes with PA by LPPs. ► The enzymatic activities observed were differently modulated. ► Our report is the first evidence of an active PA metabolism in liver nuclei.